Immunoperoxidase localization of keratin in human neoplasms: a preliminary survey. - Schlegel, R. (1980)
The distribution of intracellular keratin was studied in a variety of human tumors using a previously described immunoperoxidase technique employing antikeratin antibodies. Squamous cell carcinomas, transitional cell tumors, and mesotheliomas exhibited strong reactivity with antikeratin antibodies. Mammary adenocarcinomas were either negative or weakly positive. In the lung, an organ which can give rise to several morphologically distinct forms of carcinoma, only the squamous cell type stained strongly for keratin; undifferentiated lung carcinomas were negative, and adenocarcinomas were either negative or weakly positive. Colonic, renal, and prostatic adenocarcinomas were negative. Sarcomas, lymphomas, and neural tumors were uniformly negative. The analysis of intracellular keratin by the immunoperoxidase technique appears helpful in establishing the epithelial nature of primary or metastatic poorly differentiated neoplasms.